1986
DOI: 10.1007/bf00606666
|View full text |Cite
|
Sign up to set email alerts
|

Lack of inhibition of tolbutamide hydroxylation by cimetidine in man

Abstract: We have investigated the influence of cimetidine on the disposition of tolbutamide in 7 healthy subjects, who received 250 mg tolbutamide daily for 4 days followed by the concomitant intake of cimetidine 400 mg twice daily for a further 4 days. Cimetidine had no effect on the disposition of tolbutamide, including the unbound hydroxylation clearance rate (324 ml X min-1, tolbutamide alone; 316 ml X min-1, tolbutamide plus cimetidine). The total urinary recovery of carboxy- and hydroxy-tolbutamide metabolites wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Grygiel et al (1984) reported that while cimetidine inhibited 3-and 7-demethylation of theophylline, there was no inhibition of 8-oxidation. Dey et al (1983) found a lack of effect of cimetidine on tolbutamide plasma concentrations, which was confirmed by Stockley et al (1986), who found no change in tolbutamide hydroxylation clearance in humans. Conrad et al (1984) showed a lack of inhibition of ibuprofen clearance by cimetidine, observed a similar phenomenon with mexiletine, and Begg et al (1983) with misonidazole.…”
Section: The Cytochrome P-450 Mixed Functionmentioning
confidence: 64%
“…Grygiel et al (1984) reported that while cimetidine inhibited 3-and 7-demethylation of theophylline, there was no inhibition of 8-oxidation. Dey et al (1983) found a lack of effect of cimetidine on tolbutamide plasma concentrations, which was confirmed by Stockley et al (1986), who found no change in tolbutamide hydroxylation clearance in humans. Conrad et al (1984) showed a lack of inhibition of ibuprofen clearance by cimetidine, observed a similar phenomenon with mexiletine, and Begg et al (1983) with misonidazole.…”
Section: The Cytochrome P-450 Mixed Functionmentioning
confidence: 64%
“…Lignocaine undergoes substantial amide hydrolysis (Mihaly et al, 1978) whereas the major routes of the metabolism of bupivacaine in man are poorly documented (Tucker & Mather, 1979). The fact that cimetidine is a selective inhibitor of drug metabolism is exemplified by the finding that cimetidine impairs the 3-and 7-demethylation but not the 8-hydroxylation of theophylline (Crygiel et al, 1984), and that it is without influence on the hydroxylation of tolbutamide (Stockley et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…When cimetidine was administered at dosages of 1200 and 1600 mgjday, tolbutamide half-life and AUC increased and clearance decreased (Back et al 1988;Cate et al 1986). However, at lower doses of 800 and 1000 mgjday, cimetidine had no significant effect on tolbutamide pharmacokinetics (Back et al 1988;Dey et al 1983;Stockley et al 1986). In contrast, Adebayo & Coker (1988) reported that cimetidine 1200 mgjday had no effect on tolbutamide disposition.…”
Section: Other Agentsmentioning
confidence: 92%
“…Monitor drug Choonara et al (1986); Hetzel et al levels, adjust (1979) Toon et al (1986Toon et al ( , 1987; Wallin et al (1979) No Pachon et al (1989); Puff et al (1989); Zylber-Katz (1988) No Fraley et al (1983); Garty et al (1986); Jordaens et al (1981); Ochs et al (1984) No Harvey et al (1984) No Gugler et al (1983) No Back et al (1988); Cate et al (1986); Dey et al (1983); Stockley et al (1986) Abbreviations: C = serum/blood/plasma drug concentration; AUC = area under the concentration-time curve; t'l2 = elimination halflife; CL = clearance.…”
Section: Theophyllinementioning
confidence: 97%